2018
DOI: 10.1016/j.jacc.2018.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Outcomes of Oral Anticoagulation in Patients With Atrial Fibrillation

Abstract: DOACs were associated with a lower risk of ICH and all-cause mortality in women only, where the association of lower ICH risk remained when compared with warfarin users with good anticoagulation control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Polypharmacy was defined as the concomitant use of five or more medications 28 . In addition, a CHA 2 DS 2 ‐VASc score was calculated to estimate stroke risk 29 and a modified HAS‐BLED score (labile international normalized ratio, not included) for bleeding risk 2,30 . Finally, Charlson Comorbidity Index (CCI) was calculated to measure the mortality risk 31 …”
Section: Methodsmentioning
confidence: 99%
“…Polypharmacy was defined as the concomitant use of five or more medications 28 . In addition, a CHA 2 DS 2 ‐VASc score was calculated to estimate stroke risk 29 and a modified HAS‐BLED score (labile international normalized ratio, not included) for bleeding risk 2,30 . Finally, Charlson Comorbidity Index (CCI) was calculated to measure the mortality risk 31 …”
Section: Methodsmentioning
confidence: 99%
“…18 Another study demonstrated that in women, DOAC use was associated with a lower risk of intracranial hemorrhage and all-cause mortality when compared to warfarin. 19 Throughout their lives, women are more aware of their health status and closer to the health-care system than men; more of them consult medical doctors. 20 This also can explain why DOACs are prescribed in women more than in men-the women's drug prescriptions may be more up-todate and consistent with medical association guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the population-based retrospective cohort from the Hong Kong Hospital Authority administrative database in the Hong Kong adult diabetes population from January 1, 2006, to December 31, 2017. The Hospital Authority database has been extensively used for conducting high-quality large population-based studies [1922]. Documented diabetes mellitus diagnosis was defined as the International Classification of Primary Care, Version 2 (ICPC‐2) codes T89/T90 or International Statistical Classification of Diseases and Related Health Problems, 9th Revision, Clinical Modification (ICD‐9‐CM) codes 250.x.…”
Section: Methodsmentioning
confidence: 99%